The effectiveness of connotation to produce spatial transformation in the Iraqi theatrical performance - Lina Ismail Khalil; Asaad Abdul Redha Hussein (Basrah Arts Journal, 2024)
Place is an active and essential element in the construction and production of dramatic action because of its connection to the event. It is the place that contains the event and the action, and thus it has a psychological and semantic impact on thought and meaning. On the other hand, the place is connected to time and does not protect it from semantic manifestations and transformations. Thus, the place takes up its semantic space within the system. The theatrical presentation is an active and influential part in the structure of the event. The theatrical presentation witnessed spatial changes and variables that intertwine in the fabric of the intellectual structure to transform into connotations and symbols that carry and investigate meaning. The place was not fixed and rigid, but rather a dynamic, active variable. According to this, the research headed to monitor the effectiveness of connotation in producing transformation. Spatial within the theatrical performance.